A Portrait of the Artist as a Young/Mature Woman in Just Kids, M Train, and Year of the Monkey, by Patti Smith - SÁNCHEZ CALLE, PILAR (Miscelánea: A Journal of English and American Studies, 2023)
Patti Smith and her 2010 National Book Award-winning Just Kids offers an autobiographical account of the artist’s life with the photographer Robert Mapplethorpe. Smith also shows her involvement in New York City’s bohemian downtown scene in the 1960s and 70s. In 2015, Smith published a second memoir, M Train, and a third one, Year of the Monkey, followed in 2019. These two books are more experimental works where linear chronology is altered. The narrator mixes dream and reality in her recollection of her life after the death of her husband Fred “Sonic” Smith, and pays homage to those beloved persons (writers, artists, family members, friends) who have made an emotional and artistic impact on her. As a significant number of critical articles and book chapters have been devoted to analysing gender issues and narrative strategies of life-writing in Smith’s memoirs, my aim in this essay eschews those topics and explores the search for the artistic self as well as Smith’s ideas of art and performance in Just Kids, M Train and Year of the Monkey.
Keywords: Keywords: artistic memoir; artistic self; performance; creative partnership